Lutzomyia sand flies in the subgenus Evandromyia Mangabeira with descriptions of a new species from Brazil (Diptera: Psychodidae) () - Young, David G.; Arias, Jorge Ramon (Acta Amazonica, 1977)
The Lutzomyia sand flies in the subgenus Evandromyia Mang. are separated into two groups - the Series infraspinosa and the Series monstruosa. These are defined and the included species are catalogued. A Brasilian species, L. inpai n. sp. is described and illustrated. An identification key to the adult Evandromyia males is provided.